Employee Engagement, Lingkungan Sosial dan Kinerja Karyawan di PT Bank Rakyat Indonesia Tbk, Kantor Cabang Bogor Dewi Sartika - Minkhaya Silviana Putri; Lukman M Baga; Euis Sunarti (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Employee engagement influence the change of think pattern and behavior which supported by requirement, motivation and work satisfaction. This research aimed to study the influence of employee engagement, social environment on the employee performance in PT Bank Rakyat Indonesia (BRI). The sampling technique used in this study is a probability sampling , the number of respondents used is 83. The method use multiple regression analysis. The result show of based on employee engagement and social environment the temporary employee have the higher performance than permanent employee. The woman temporary employee have the higher performance than man temporary employee. The component  of employee engagement and social environment influenced performance is camaraderie that is employee relationship, team cooperation and motivation. Therefore, PT BRI must took care of good relationship inter employee and increase team cooperation